Extraction of peanut skin oil by modified supercritical carbon dioxide: Empirical modelling and optimization - Putra, N.R. (Taylor and Francis Inc., 2018)
Peanut skin is a waste by-product from peanut industries. It is rich in antioxidants and bioactive compounds. Therefore, the objective of this study was to empirically model and optimize supercritical CO2 extraction of oil from peanut skin. The extraction conditions were pressure (100, 200 and 300 bar), temperature (313, 328 and 343Â K) and rate of modifier ethanol (0.075, 0.15 and 0.225Â mL/min). The extraction process was subsequently examined using modified Brunner and Esquivel models. The optimum conditions for extraction peanut skin oil were 279 bar, 70Â°C and rate of modifier of 7.5 with a maximum yield of peanut skin oil of 0.83Â g and initial slope of 0.568Â g/min. Â© 2018 Taylor & Francis